A tale of two conformers: spectroscopic evidence for halide catalysed formic acid isomerisation. Issue 40 (5th October 2022) - Haakansson, Christian T.; Corkish, Timothy R.; Watson, Peter D.; Robinson, Hayden T.; Brookes, James R.; Adam, Hannah C.; McKinley, Allan J.; Wild, Duncan A.
Abstract : Halide anions are experimentally and theoretically shown to preferentially stabilise the higher energy formic acid conformer. Moreover, halide anions appear to lower the isomerisation barrier associated with conformer interconversion. Abstract : Halide–formic acid complexes have been studied utilising a combined experimental and theoretical approach. Formic acid exists as two conformers, distinguished by the relative rotation about the C–OH bond. Computational investigation of the formic acid isomerisation reaction between the two conformers has revealed the ability of halide anions to catalyse the formation of, and preferentially stabilise, the higher energy conformer. Anion photoelectron spectroscopy has been used to study the halide–formic acid complexes, with the experimental vertical detachment energies compared with simulated photodetachment energies with respect to halide complexes with both formic acid conformers. The existence of experimental spectral features associated with halide complexes of the higher energy formic acid confomer confirms in situ generation, likely as a result of the halide mediated catalytic formation.